Fluorinated betulinic acid derivatives and evaluation of their anti-HIV activity. Issue 1 (1st January 2016) - Li, Jizhen; Goto, Masuo; Yang, Xiaoming; Morris-Natschke, Susan L.; Huang, Li; Chen, Chin-Ho; Lee, Kuo-Hsiung
Graphical abstract: Abstract: Several fluorinated derivatives of the anti-HIV maturation agent bevirimat (1 ) were synthesized and evaluated for anti-HIV replication activity. The modified positions were the C-2, C-3, C-28, and C-30 positions, either directly on the betulinic acid (2 ) skeleton or in the attached side chains. Compound18, which has a trifluoromethyl group added to C-30 of its isopropenyl group, exhibited similar potency to1 against HIV-1NL4-3 . In total, our current studies support our prior conclusion that C-30 allylic modification is unlikely to be a pharmacophore for anti-HIV activity, but could be a meaningful route to manipulate other properties of2 -related compounds.